Representative Versus Direct Democracy in Regional Head Elections: A Constitutional Analysis of Popular Sovereignty in Indonesia - Ridho Harapan Bunda; Muhammad Fadli; Resti Hefriyenni (Magister of Law, Faculty of Law, Universitas Islam Sultan Agung, 2026)
The discourse on returning the election of regional heads to the Regional People’s Representative Council (DPRD) has resurfaced in Indonesia’s constitutional debate, gaining significant support from major factions in the national parliament. This proposal is primarily driven by the exponential rise in political costs and widespread money politics, which are viewed as eroding the integrity of direct elections. What began as a procedural debate has now evolved into a fundamental discussion about the most suitable model of local democracy in light of Indonesia’s current political realities. This study examines the discourse through constitutional analysis, positioning popular sovereignty as the central normative variable while assessing its implications for local democracy quality. Using statutory and conceptual approaches, the research analyzes laws and democratic doctrines. The findings indicate that the phrase “elected democratically” in Article 18 paragraph (4) of the 1945 Constitution allows flexible interpretation, accommodating both direct and indirect election models. However, returning authority to the DPRD risks consolidating local political oligarchies, weakening legislative oversight, and limiting public participation. Ultimately, the dysfunction in local democracy stems not primarily from the direct election system, but from institutional weaknesses, declining political ethics, and low accountability of democratic actors.